Estudio de la reducción de la población de plagas mediante el uso de la trampa solar - Rea Tutín, Ángel Nazareno (2016)
The research was conducted in the Atocha community, Salcedo canton, with the aim of determine the reduction of pest populations by building a solar trap; the methods used are observation allowed to know the behavior of pests to the incidence of light emitted by the traps, the experimental method facilitated the handling of samples in the laboratory using the stereoscope and entomological guides to know the characteristics taxonomic insects. Averages in order to know the abundance of pests associated with (Solanum tuberosum) in physiological crop stages (development, flowering and ripening) was presented. From the results, 10 species of nocturnal insects that cause damage to the potato crop and are recorded in botanical records identified.